Reconceptualizing English Education in a Multilingual Society English in the Philippines - Martin, Isabel Pefianco (Singapore Springer Singapore Imprint: Springer, 2018)
This book brings together chapters that describe, investigate, and analyze the place of English in education in multilingual Philippines. Unlike most studies on languages in education, which take a neutral, de-contextualized stance, this volume take a pluricentric view of the English language by positioning it in relation to its varieties, as well as to other languages in the country. Because of the changing realities of English in the Philippines, traditional assumptions about the language as monolithic and unchanging, as well as about how it should be taught and learned, need to be revisited and re-conceptualized.
Introduction -- 1 Re-conceptualizing English education in multilingual Philippines -- Part 1 English: Policy, Ideology, and Identity -- 2 English in multilingual settings: Features, roles and implications -- 3 The supremacy of English in Philippine language education policy -- 4 Critiquing Mother Tongue-based language-in-education Policies: A focus on the Philippines -- 5 Anguish as Mother Tongue: English in a multilingual context -- 6 Teacher ideology in English Language Education -- Part 2 Teaching English, Teaching in English -- 7 An endocentric approach to English Grammar teaching -- 8 Using Filipino in an English classroom: Teaching with resistance and relevance -- 9 English in the teaching of Mathematics: Policies, realities, and opportunities -- 10 The technicist framework and the teaching of speech communication in the Philippines -- 11 Migrant workers, language learning, and spaces of globalization: The case of Filipino Maritime Professionals -- Synthesis -- 13 English in Education in the Philippines: From research to policy.
Description based on publisher-supplied MARC data.
Keywords: Language and education